Potential Adoption and Commercial Introduction of GM Crops in Finland: A Case Study on Potato - Niemi, Jyrki; Tuomisto, Jussi (Center for Promoting Ideas (CPI), USA, 2019)
This paper analyses the possible adoption and commercial introduction of genetically modified (GM) crops in Finland. It is divided into two main parts. First and foremost, based on the available literature, the economic and policy factors which influence the rate of adoption and diffusion of GM technology in agriculture are examined. Secondly, the potato is used as a case study to provide further insights into economic and strategic issues plus the implications of adopting GM technology within the Finnish agri-food chain. The case study is based on interviews with key players involved in farming, processing, trade, and the administration of the production of potato.The results suggest that GM technology will not alter the basic structure of agri-food industry, but will create changes in the cost and benefit distribution. In addition, an increased use of contractual arrangements will lead to greater vertical integration and co-ordination in the value chain of potato.
Keywords: biotechnology; technology adoption; genetically modified crops; potato; food chains; regulations